Buruli ulcer: The Efficacy of Innate Immune Defense May Be a Key Determinant for the Outcome of Infection With Mycobacterium ulcerans - Röltgen, Katharina; Pluschke, Gerd (Frontiers in Microbiology, 2020)
Buruli ulcer (BU) is a neglected, tropical infectious disease of the skin and the subcutaneous tissue caused by Mycobacterium ulcerans. This pathogen has emerged as a new species from a common ancestor with M. marinum by acquisition of the virulence plasmid pMUM. The plasmid encodes enzymes required for the synthesis of the macrolide toxin mycolactone, which has cytotoxic and immunosuppressive activities. In advanced BU lesions, extracellular clusters of M. ulcerans reside in necrotic subcutaneous tissue and are protected from infiltrating leukocytes by the cytotoxic activity of secreted mycolactone. Several lines of evidence indicate that elements of the innate immune system eliminate in many cases the initial inoculum and that therefore exposure to M. ulcerans leads only in a minority of individuals to the characteristic chronic necrotizing BU lesions. It is assumed that phagocytes play a key role in early host defense against M. ulcerans. Antibodies against bacterial surface structures seem to have less potential to enhance innate immunity than TH1 cell responses. Precise immune effector mechanisms leading to protective immunity are however unclear, complicating the development of effective vaccines, the most desired solution to control BU. The tuberculosis vaccine M. bovis Bacillus Calmette-Guérin (BCG) has limited short-term protective activity against BU. Current vaccine research and development activities are focusing on recombinant BCG, subunit vaccines with selected M. ulcerans proteins, and the neutralization of mycolactone.